Overexpression of mmpS5/mmpL5 in Mycobacterium tuberculosis reduces susceptibility to anti-tuberculosis drugs - Scott, Leere Ann (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc) -- Stellenbosch University, 2022.